Proteomic profiling of sweat in patients with cystic fibrosis provides new insights into epidermal homoeostasis - Matthieu Cornet; Thao Nguyen‐Khoa; Mairead Kelly‐Aubert; Vincent Jung; Frédérique Chedevergne; Muriel Le Bourgeois; Laura Aoust; Kévin Roger; Chiara Ida Guerrera; Isabelle Sermet‐Gaudelus (Wiley, 2023)
Abstract Background A high proportion of patients with Cystic Fibrosis (CF) also present the rare skin disease aquagenic palmoplantar keratoderma. A possible link between this condition and absence of a functional CF Transmembrane conductance Regulator protein in the sweat acinus and collecting duct remains unknown. Methods In‐depth characterization of sweat proteome profiles was performed in 25 CF patients compared to 12 healthy controls. A 20 μL sweat sample was collected after pilocarpine iontophoresis and liquid chromatography tandem mass spectrometry (LC‐MS/MS) proteomic analysis was performed. Results Sweat proteome profile of CF patients was significantly different from that of healthy subjects with 57 differentially expressed proteins. Cystic Fibrosis sweat proteome was characterized by an increase in 25 proteins including proteases (Kallikrein 7 and 13, Phospholipase B domain containing 1, Cathepsin A L2 and B, Lysosomal Pro‐X carboxypeptidase); proinflammatory proteins (Annexin A2, Chitinase‐3‐like protein 1); cytochrome c and transglutaminases. Thirty‐two proteins were downregulated in CF sweat including proteases (Elastase 2), antioxidative protein FAM129 B; membrane‐bound transporter SLC6A14 and regulator protein Sodium‐hydrogen antiporter 3 regulator 1. Conclusion This study is the first to report in‐depth characterization of endogenous peptides in CF sweat and could help understand the complex physiology of the sweat gland. The proteome profile highlights the unbalanced proteolytic and proinflammatory activity of sweat in CF. These results also suggest a defect in pathways involved in skin barrier integrity in CF patients. Sweat proteome profile could prove to be a useful tool in the context of personalized medicine in CF.